HYBRID FUZZY LOGIC AND VECTOR CONTROL OF PERMANENT MAGNET SYNCHRONOUS MOTOR DRIVE FOR ELECTRIC VEHICLE - GHODBANE, H.; KRAA, O.; ABOUBOU, A.; A. TALEB, A. (Courrier du Savoir; Vol. 15 (2013): Courrier du Savoir)
This  paper  presents  the modelling  and  the  control  of  a Permanent Magnet Synchronous Motor  (PMSM)  speed used  in an electric vehicle. The classical vector control technique is enhanced using a speciﬁc Fuzzy Logic Controller FLC instead of a simple PI, IP or PID control. These classical controllers need the adjustment of controller gains. The determination the gains is not easy and needs  to be adjusted  if  the operating conditions change. The optimization problem of regulators IP parameters used  in  the  vector  control method,  has  been  solved  by  using  a Fuzzy Logic. The FLC  can  be  dedicated  entirely  to  vector control  of PMSM  and  it  offers  a  robust  and  a  realizable  controller  acting  as  a  non  linear  (and  optimized) PID. Than,  the combination of fuzzy control strategy with vector controlled can give a good combination. In order to validate the simulation results, a comparison between  the  results obtained by classical vector control and the presented hybrid controller using FLC obtained by Matlab/Simulink software tool is included.